Social protection of the rural population in terms of land reform - Шатохін, А. М.; Вуйченко, М. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
The article outlined the results of sociological monitoring of the 2011-2016. social well-being and social protection of the rural population in terms of land reform in Ukraine. Analysis of the changes in the attitude of the peasants to the socio-economic, socio-political and socio-cultural processes taking place in Ukraine lately, identified the most acute problems of rural living environment, a sense of social protection in terms of land reform. Noted significant problems in ensuring the constitutional order, the protection of human rights to secure livelihoods, employment, welfare. Found that over the past years are positive changes in the attitude of farmers to purchase agricultural lands increases the share of supporters raising lands in market circulation.